2021
DOI: 10.3389/fphar.2021.630970
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Changes of Pharmacokinetics Behaviors of Phytochemicals and the Influence on Endogenous Metabolites After the Combination of Radix Bupleuri and Radix Paeoniae Alba Based on Multi-Component Pharmacokinetics and Metabolomics

Abstract: Radix Bupleuri-Radix Paeoniae Alba (RB-RPA) is a classic herb pair, which is commonly used to treat depression by soothing “liver qi stagnation” in the clinic. However, little is yet known concerning the combination mechanism of Radix Bupleuri (RB) and Radix Paeoniae Alba (RPA), their bioactive forms in vivo and the regulatory effects on the organism. The present study aimed to elucidate the changes in multi-component pharmacokinetics (PK) behavior after the combination of RB and RPA by a high-resolution full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In clinical applications, BR has been widely used for treatment of fever, pain, and inflammation associated with influenza or the common cold ( Yang et al, 2017 ). The modern pharmacological investigations reported that BR presented broad biological activities including anti-influenza ( Yan et al, 2022 ), anti-tumor ( Zhao et al, 2019 ; Zhou et al, 2021 ), anti-inflammation ( Jiang et al, 2020 ), anti-depression ( Guo et al, 2020 ; Chen et al, 2021 ), anti-stress ( Wang P. et al, 2021 ; Wang Z. et al, 2021 )and antipyretic ( Wang et al, 2019 ), antiviral ( Du et al, 2018 ), antimicrobial ( Liu et al, 2016 ), immunomodulatory ( Tang et al, 2021 ) and hepatoprotective effects ( Ren et al, 2019 ). Although different types of chemicals have been reported to contain in BCH (saponins, volatile oils, flavonoids and polysaccharides) ( Xing et al, 2015 ) and NCH (saponins, lignans, fatty acids, volatile oils and polysaccharides) ( Jiang et al, 2020 ), the saponins and volatile oils have been investigated to be the most important parts for both BR species which are associated to their antipyretic ( Xing et al, 2015 ; Li et al, 2018 ) and anti-inflammatory effects ( Kim et al, 2015 ; Ma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical applications, BR has been widely used for treatment of fever, pain, and inflammation associated with influenza or the common cold ( Yang et al, 2017 ). The modern pharmacological investigations reported that BR presented broad biological activities including anti-influenza ( Yan et al, 2022 ), anti-tumor ( Zhao et al, 2019 ; Zhou et al, 2021 ), anti-inflammation ( Jiang et al, 2020 ), anti-depression ( Guo et al, 2020 ; Chen et al, 2021 ), anti-stress ( Wang P. et al, 2021 ; Wang Z. et al, 2021 )and antipyretic ( Wang et al, 2019 ), antiviral ( Du et al, 2018 ), antimicrobial ( Liu et al, 2016 ), immunomodulatory ( Tang et al, 2021 ) and hepatoprotective effects ( Ren et al, 2019 ). Although different types of chemicals have been reported to contain in BCH (saponins, volatile oils, flavonoids and polysaccharides) ( Xing et al, 2015 ) and NCH (saponins, lignans, fatty acids, volatile oils and polysaccharides) ( Jiang et al, 2020 ), the saponins and volatile oils have been investigated to be the most important parts for both BR species which are associated to their antipyretic ( Xing et al, 2015 ; Li et al, 2018 ) and anti-inflammatory effects ( Kim et al, 2015 ; Ma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CUMS program was performed as previously described, with some modifications. , With the exception of the control group, rats in the other groups were exposed to one of the following chronic unpredictable mild stressors in random order daily for four weeks: swimming in cold water (4 °C) (5 min), banning water (24 h), 50 °C exposure (10 min), tail clamping for 2 min, fasting (24 h), ultrasound stimulation (60 MHz) (3 h), restraint (3h), foot shock every 10s (2 min), and breaking circadian rhythms . At the same time, rats were kept separately under the same conditions except for the control rats, which were kept undisturbed in their cages.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that sFF&sPF group had the best efficacy in the treatment of diarrhea and polyuria, and salt treatment would briefly affect the correlation between pharmacodynamic components and endogenous metabolites. Chen et al (2021) used pharmacokinetics and metabolomics, relying on UHPLC-Q Exactive Orbitrap-MS technology, to elucidate the compatibility mechanism of Radix Bupleuri-Radix Paeoniae Alba (RB-RPA). The results showed that the RB-RPA combination could dramatically enhance the bioavailability of 11 drug ingredients and raise neuroprotective and anti-inflammatory activity.…”
Section: Formula Compatibilitymentioning
confidence: 99%